Lead-Related Genetic Loci, Cumulative Lead Exposure and Incident Coronary Heart Disease: The Normative Aging Study. - Ning Ding; Xin Wang; Marc G Weisskopf; David Sparrow; Joel Schwartz; Howard Hu; Sung Kyun Park (PLoS ONE)
Background Cumulative exposure to lead is associated with cardiovascular outcomes. Polymorphisms in the δ-aminolevulinic acid dehydratase (ALAD), hemochromatosis (HFE), heme oxygenase-1 (HMOX1), vitamin D receptor (VDR), glutathione S-transferase (GST) supergene family (GSTP1, GSTT1, GSTM1), apolipoprotein E (APOE),angiotensin II receptor-1 (AGTR1) and angiotensinogen (AGT) genes, are believed to alter toxicokinetics and/or toxicodynamics of lead. Objectives We assessed possible effect modification by genetic polymorphisms in ALAD, HFE, HMOX1, VDR, GSTP1, GSTT1, GSTM1, APOE, AGTR1 and AGT individually and as the genetic risk score (GRS) on the association between cumulative lead exposure and incident coronary heart disease (CHD) events. Methods We used K-shell-X-ray fluorescence to measure bone lead levels. GRS was calculated on the basis of 22 lead-related loci. We constructed Cox proportional hazard models to compute adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for incident CHD. We applied inverse probability weighting to account for potential selection bias due to recruitment into the bone lead sub-study. Results Significant effect modification was found by VDR, HMOX1, GSTP1, APOE, and AGT genetic polymorphisms when evaluated individually. Further, the bone lead-CHD associations became larger as GRS increases. After adjusting for potential confounders, a HR of CHD was 2.27 (95%CI: 1.50-3.42) with 2-fold increase in patella lead levels, among participants in the top tertile of GRS. We also detected an increasing trend in HRs across tertiles of GRS (p-trend = 0.0063). Conclusions Our findings suggest that lead-related loci as a whole may play an important role in susceptibility to lead-related CHD risk. These findings need to be validated in a separate cohort containing bone lead, lead-related genetic loci and incident CHD data.